(3ZT GdNUhe cSHH dGdJeGS EYGOI GdfXQ aj VhA bGfhf GdeQGaYGJ Gdjefj Qbe (B(40) (3dSfI (B2002 : s (3OQGSI ebGQfI (B/ s - (3UGOb jMjj Ydj GdYQjs; (3CSGeI CMeO Thbi GdedjLis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JfGhdJ gPg GdOQGSI ZT GdNUhe cSHH dGdJeGS EYGOI GdfXQ(B: (3hJWQbJ HOGjI dHjGf eGgjI GdWYf HGdGdJeGS MjK JWQbJ ajgG Edi HjGf eaghe GdGdJeGS heG jejRg Yf ZjQg(B: (3heG GdCSHGH GdJj JDOi Edi GdGdJeGS(B: (3hELQGAGJg hBKGQg? Ke JfGhdfG HYO Pdc eGgjI GdZT GdeHQQ ddGdJeGS(B: (3heG jejRg Yf ZjQg(B: (3hGdeaJQVGJ GddGReI ddWYf ai GdMce HGdGdJeGS Ydi CSGS GdZT(B: (3ShGA GdeJYdbI HGdNUhe Ch GdeJYdbI HGdCMcGe(B: (3Ke JfGhdfG HYO Pdc YfGUQ GdZT GdeJeKdI ai GdYfUQ GdeGOi hGdeYfhi(B: (3hCge UhQ GdZT GdeHQQ ddGdJeGS(B. (3Ke JWQbJ GdQSGdI HYO Pdc dWQb EKHGJ GdZT hef GdTNU Gdecda HYHA GdEKHGJ(B: (3heMd GdEKHGJ(B: (3hWQb EKHGJ GdZT, heG gh GdeYjGQ GdPi jJe GdGYJeGO Ydjg ai GKHGJ GdZT(B: (3Ke GNJJeJ gPg GdQSGdI HGdhSGFd GdJi QCi GdHGMK ef NdGdgG Cfg jecf Cf fMO ef gPg GdXGgQI GdJi CUHMJ JDQb GdeLJeY(B: (3Ke GNJJeJ gPg GdOQGSI HGdfJGFL hGdJhUjGJ GdeJhGVYI(B: (3hGdJi QCi GdHGMK CfgG bO JSge ai GdMO ef XGgQI GdZTs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe bGfhf GdYGe, (B2014s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B513-546s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdGdJeGS s; (3GdNUhe s; (3GdZT s; (3GdWYfs; (3GdNUheIs; (3GdMjds; (3GdbGfhf Gdjefjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes